Anonymous Online Offenders – Presumption of Innocence or Presumption of Guilt? A Comparative Analysis between the Evidence Act 1950 and the Islamic Criminal Law - Nazli, Ismail@Nawang (2017)
Anonymity is perhaps the most valued feature of the Internet as its users are able to conceal their true identities or assume pseudonyms in the cyber world. Anonymity may be good for freedom of speech as any speakers could freely express their thoughts without the fear of being identified (though not impossible). Unfortunately, anonymity poses great challenges to law enforcement agencies as they would face difficulty in tracing cyber offenders. For that reason, the Malaysian Parliament has passed a new section 114A of the Evidence Act 1950 that has the effect of shifting the burden of proof on the alleged offenders to prove his innocence. This provision seems to be in contrast with the legal maxim of ‘semper necessitas probandi incumbit ei qui agit’ which means ‘he who asserts must prove’. This same principle has also been adopted in Islamic criminal law as the Islamic legal maxim has explicitly stated that ‘the onus of proof is upon the claimant, and the taking of an oath is upon him who denies’. As such, this paper attempts to scrutinise the approach that has been adopted by judges in interpreting and applying this new law. Further, a comparative analysis with Islamic criminal law will be made in order to ascertain whether such principle could be applied in certain cases since cyber criminals are hardly traceable or identifiable. The study is largely based on doctrinal research as it is primarily concerned with the review of relevant decided cases and statutory provisions as well as text books, journal articles and seminar papers. To sum up, it is submitted that the new law does not amount to an automatic presumption of guilt as the prosecutors are still required to prove the existence of relevant basic facts before the accused is mandated to prove his innocence.